PENYELESAIAN KONFLIK SOSIAL DALAM NOVEL HEMPASAN GELOMBANG KARYA TAUFIK IKRAM JAMIL - Indiana, Poppy Indiana Poppy; Rahman, Elmustian Rahman Elmustian; Rumadi, Hadi Rumadi Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRAK: This study discusses the settlement of social conflictin thenovel Hempasan Gelombang opus Taufik Ikram Jamil. The method used in thisresearch is descriptive qualitative method that aims to describe the social conflictand resolution in the novel Hempasan Gelombang opus Taufik Ikram Jamil. Thedata used in this study is qualitative data in the form of dialogue and statementsderived from a novel written by Taufik Ikram Jamil, this novel titled HempasanGelombang, published by the Department of Culture and Tourism of Riau in2009. Data social conflicts found in the Hempasan Gelombang opus Taufik IkramJamil amounted to 22 conflicts among nine individual conflict with it self, theconflict there were 11 individuals with individual conflicts and individual conflictswith the social environment there are 2 conflicts. Conflict resolution found usingmultiple okomodasi including integration, tolerance, coercion, and eliminatoin,there are also some conflicts that none of its solution. Thus, it can be concludedthat the settlement of social conflict in the novel Hempasan Gelombang opusTaufik Ikram Jamil by way of integration, tolerance, coercion, and eliminatoin,there are also some conflicts that none of its solution.Keywords: Conflict, Social, Novel Hempasan Gelomban